Marketing, Creativity and Experiential Design. - Matos, Nelson de (Cambridge Scholars Publisher, 2021)
This book serves to help students and practitioners to understand and explore marketing and design by looking at the sphere of marketing, experiential design and innovation and providing an overview of experience marketing frameworks and innovation's role in the economy. It also explores branding, identity and product-service design and digital marketing, interaction design and human-centred design. The book details research methodology developments in design management and marketing, and considers future avenues for marketing, creativity and experiential design.